Late Glacial Hunter-Gatherers in Westphalia - The Final Paleolithic Site of Salzkotten-Thüle (District of Paderborn, North Rhine-Westphalia, Germany) - Heidenreich, Stephan (Archäologische Informationen, 2009)
The fi nal Paleolithic site of Salzkotten-Thüle, district of Paderborn, was discovered and excavated in 2001 during the excavation of a Germanic settlement of the fi rst century AD. The fi nds are composed of stone objects only, of which ca. 80 % can be designated as artifacts, while ca. 20 % are natural chunks and thermally altered chunks. Locally available Baltic fl int was the main employed raw material (ca. 95 %), while keratophyre and siliceous schist were only used in small amounts. The technological analysis led to the reconstruction of an opportunistic reduction sequence without clearly separated stages of preparation and blank production. Meanwhile, the set of stone tools is characteristic for a northwestern European Federmesser-site. Both typology and technology place the site within a rather late stage of the Federmesser-groups between the second half of the Allerød-Interstadial and the beginning of the Younger Dryas, i. e. between ca. 11,500 and 10,800 calBC. Besides the technological and typological analysis, the examination also included a spatial analysis, which led to two different models of site structure. The existence of a dwelling is of great importance for interpretatio